Bahasa Indonesia - Yeni, Yeni; Supandi, Supandi; Khalishah, Yulianindra (Universitas Muhammadiyah Prof. Dr. Hamka, 2018)
Coumarin derivative compounds show anti-blood coagulation activity, inhibits the action of enzymes, antimicrobial, antibiotics, and anti-cancer by interfering the synthesis of DNA / RNA. This study aims to obtain quantitative structure-activity relationship, coumarin derivatives against colon cancer receptors with Hänsch approach through multilinear analysis, able to make modifications compounds based on QSAR equation in an attempt to enlarge the potency and selectivity of drugs. Descriptors were selected to represent the electronic, hydrophobic and steric parameters. Molecular Docking done by using Autodock Vina to analyze the interaction within coumarin derivatives and the topoisomerase II enzyme. The results obtained QSAR equation has been validated by the method LOO (Leave One Out) is Log IC50 = -4.047+ (0496 x AM1_dipol) + (-0089 x AM1_HOMO) + (0899 x logP    (o / w)) + (0.903 x logs) + (0.351 x mr). The results showed IC50 prediction of modificated compounds(MOD2) with NO2 substituents have the best activity with the lowest ΔGbind -8.8 kcal / mol and has the smallest prediction IC50 1.0897 μM compared to IC50 lead compound (C14),  that is 1.77 μM.